Transparency of Information and Public Participation in Energy Transition - Firdaus Cahyadi; Soeryo Adiwibowo; Edy Hartulistiyo (Jurnal Penelitian Pendidikan IPA, 2025)
The Just Energy Transition Partnership (JETP) initiative, a climate finance mechanism spearheaded by France, Germany, the United Kingdom, the United States, and the European Union, was established at the 26th Conference of the Parties (COP26) in Glasgow, England, in 2021. The JETP framework, specifically emphasized the participation of non-state actors, including Civil Society Organizations (CSOs), in achieving the objectives of the Paris Agreement. Following its initial launch, a JETP agreement was subsequently established for Indonesia in 2022, coinciding with the G20 Summit in Bali. This study examines the role of CSOs in influencing the energy transition policy discourse surrounding the JETP initiative in Indonesia, with a particular emphasis on their impact on policy formulation through media engagement. To this end, a comprehensive discourse analysis was conducted on 134 articles sourced from ten Indonesian online media outlets, published between August 2020 and June 24, 2024. The analytical methodology involved the application of Discourse Network Analysis (DNA) software to map discourse patterns, and the utilization of the MICMAC (Matrix of Crossed Impact Multiplications Applied to a Classification) software to identify dominant discourse themes. The analysis revealed that transparency and public participation emerged as critical factors significantly influencing the formulation of energy transition policies within the JETP framework.